Gaming programs for all ages at the library a practical guide for librarians - Bruno, Tom 1972- (Practical guides for librarians, 2018)
"Gaming Programs for All Ages at the Library shows you how you can launch and support gaming programming in your library. Everything from acquisitions to budgeting to circulation is covered in this practical guide, as well as promotion, assessment, and experiential learning opportunities"-- Provided by publisher.